The Role of Trade Costs in the Russian-Paraguayan Trade Relations - Ryzhkova, Valeriia S.; Koval, Alexandra G. (Latin American Journal of Trade Policy, 2019)
The changed geopolitical situation and deterioration of Russia-West relations has induced the expansion of trade and economic cooperation between Russia and Latin American countries. Currently, Paraguay is explicitly showing its readiness to strengthen recently built trade relations with Russia. In order to fuel their increased mutual interest, it is crucial to struggle with impediments that hinder the trade between them. The export potential assessments demonstrate that Russia and Paraguay indeed have potential to intensify bilateral trade, even though the opportunities for export diversification are quite limited. The authors conduct a survey to identify the major trade costs and their role in the development of the Russian-Paraguayan trade relations. The survey findings reveal that transportation and logistics costs significantly impede the exports of both countries as well as information-related obstacles represent the top concern for Russian export companies, while non-tariff measures, language and cultural barriers are relevant for Paraguayan firms. In order to intensify the Russian-Paraguayan commercial relations, the policy makers could deal with these barriers via a higher exchange of market information through different institutional channels.